Social Media Influencers Defined by Adolescents - Zozaya Durazo, L.D.; Feijoo, Beatriz; Sádaba, Charo (KOME: An International Journal of Pure Communication Inquiry, 2023)
Social media influencers have emerged as digital celebrities, positioning themselves as role models for different audiences, particularly young people. Due to the inherent social and psychological immaturity of adolescents, they are considered a more vulnerable group, and thus, their digital behaviour and its potential impact on their identity development should be carefully studied. This study aimed to explore how adolescents perceive social media influencers. Sixtytwo adolescents between the ages of 11 and 17 living in Spain participated in 12 focus groups. The study attempted to understand how adolescents define the concept of social media influencers and which profiles they follow in order to identify the attributes they prioritised. This study describes the categories proposed by the adolescents, as well as the influence generated by social media influencers based on the age and socio-economic status of the interviewees. Additionally, the study reveals that adolescents from lower socio-economic levels and adolescents between 16 and 17 years old expressed a desire to become social media influencers.
Keywords: social media influencer; social media; entertainment; followers; parasocial relationship; brands; adolescents